Increased 21-hydroxylase and shutdown of C17,20 lyase activities in testicular tissues of the grouper (Epinephelus coioides) during 17α-methyltestosterone-induced sex inversion - Lee, S.T. (2014)
10.1016/S0016-6480(02)00005-9